Short-term effects of a Rigid Interocclusal Appliance and Hypnosis on individuals with bruxism: a feasibility study for a randomized clinical trial - Henrique dos Reis-Prado, Alexandre; Maria Botelho, Adriana; Valadares Roquete Maia, Cláudia; Carolina Coelho de Oliveira, Ana; Evangelista Cordeiro, Jane; Pena Botelho, Letícia; Leonan da Silva, Brender; Galo, Rodrigo; Willya Douglas de Oliveira, Dhelfeson (Revista Vozes dos Vales: Publicações Acadêmicas, 2024)
This study had the aim of evaluate the feasibility of a randomized clinical trial to compare the effects of a Rigid Interocclusal Appliance and Hypnosis on the quality of life and muscle pain in individuals with bruxism. Forty-two patients with self- report bruxism and clinical examination were randomly assigned to three groups: Rigid Interocclusal Appliance (G1), Hypnosis (G2), and a Control Group (G3). Data collection occurred at baseline and 40 days after the interventions using the Oral Health Impact Profile (OHIP-14), Lip’s Inventory of Stress Symptoms (ISSL) and muscle and joint palpation. P-value < 0.05 was considered significant. The G1 showed a greater reduction in pain in the masseter’s portions and in the temporalis tendon insertion (p<0.05). No significant differences were observed in the quality of life (OHIP-14). From this pilot study it was possible to verify the feasibility of a clinical trial with a larger sample size and follow-up time.